Do Youth Nonmarital Childbearing Choices Reflect Expected Income and Relationship Consequences? - Wolfe, Barbara; Haveman, Robert; Pence, Karen; Schwabish, Jonathan (My University, 2006)
The authors explore whether the perceptions unmarried, adolescent females have about the consequences of choices they make affect those choices and the teens' behavior. The analysis considers expectations about marriage and cohabitation and about income.